The microlepidopterous natural enemy Brachymeria subrugosa Blanchard, 1942 (Hymenoptera, Chalcididae): identity, hosts and geographic distribution - Aquino, Daniel Alejandro; Tavares, Marcelo Texeira; Balducci, Ezequiel; Baca, Verónica; Quinteros, Sara Quintana De (Zootaxa, 2015)
A lectotype is designated for Brachymeria subrugosa Blanchard 1942 (Hymenoptera: Chalcididae). The species is diagnosed, redescribed, and compared to B. subconica Bouček, both of which are illustrated by macrophotography. Taxonomic notes, new parasitoid/host associations and new geographical records are also given for B. subrugosa. Brachymeria annulipes (Costa Lima 1919), a junior secondary homonymy of Chalcis annulipes Walker 1834, is proposed as a junior synonym of B. subrugosa syn. nov.